Assessing the ability of the 14C projection-age method to constrain the circulation of the past in a 3-D ocean model - Franke, J.; Schulz, M.; Paul, A.; Adkins, J. F. (Geochemistry, Geophysics, Geosystems, 2008)
Radiocarbon differences between benthic and planktonic foraminifera (B-P ages) and radiocarbon projection ages are both used to determine changes of the past ocean circulation rate. A global 3-D ocean circulation model with a constant modern ocean circulation is used to study which method is less influenced by atmospheric Δ14C variations. Three factors cause uncertainties: first, the long equilibration time of the ocean after atmospheric Δ14C changes; second, different mixing processes in the ocean, which cause an ocean response of smaller amplitude than the atmospheric forcing; and third, the unknown source region and corresponding initial surface 14C reservoir age of subsurface waters. The model suggests that B-P ages and projection ages have lower uncertainties the closer they are to deepwater formation zones. In the North Atlantic the B-P age method is less influenced by atmospheric Δ14C variations than the projection-age method. Projections ages vary less in the Pacific as long as atmospheric Δ14C decreases linearly. A more irregular atmospheric Δ14C evolution leads to age variations of similar magnitude with both methods. On the basis of the model experiment, we suggest a potential improvement of the projection-age method.